Impact of the Antidiabetic Drug Metformin and Its Transformation Product Guanylurea on the Health of the Big Ramshorn Snail (Planorbarius corneus) - Jacob, Stefanie; Köhler, Heinz-R.; Tisler, Selina; Zwiener, Christian; Triebskorn, Rita (Frontiers in Environmental Science, 2019)
Pharmaceuticals can enter surface waters via sewage treatment plants. In the environment, the substances and their transformation products, formed by degradation of the parent compounds, may affect aquatic wildlife including freshwater invertebrates. However, research on pharmaceutical-induced effects in feral freshwater organisms other than fish is still scarce to date. In our study, we therefore investigated the impact of the highly consumed antidiabetic drug metformin and its main transformation product guanylurea on the health of a freshwater gastropod – the big ramshorn snail (Planorbarius corneus) with respect to biochemical and cellular stress responses and apical parameters. The snails were exposed to different concentrations of the drug (0, 10, 100, 1000, 10 000, 100 000 µg/L) and its transformation product (0, 100, 10 000, 100 000 µg/L). The examined parameters were mortality, weight, tissue integrity of the hepatopancreas and the levels of stress proteins and lipid peroxides. Mortality and the levels of stress proteins and lipid peroxides were not influenced by the two substances. In response to the highest concentrations of both chemicals, the weight of the snails was slightly but not significantly reduced. The histopathological investigation of the hepatopancreas revealed a significant effect of guanylurea at a concentration of 100 000 µg/L with an increased number of symptoms of cellular responses in the tissue (e.g. dilated lumen, disturbed compartmentation of the digestive cells, nucleus deformation, hyperplasia and hypertrophy of crypt cells). For the parent compound, a similar trend was also revealed for the highest concentration. Overall, the observed effects did not occur at environmentally relevant concentrations, but at concentrations which were 10 000 times higher than these. Thus, the results did not give rise to major concern that metformin and guanylurea may pose a risk to the big ramshorn snail in the environment.